PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BASIC MATERIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fita Rizki; Hamida Sari Siregar (Smart Education, 2026)
Abstract: This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) on firm value in Basic Materials sector companies listed on the Indonesia Stock Exchange during the period 2021–2023. Firm value is proxied by Price to Book Value (PBV). The data used are secondary data obtained from annual financial statements. The sample consisted of 15 companies over a three-year observation period (2021–2023), resulting in 45 observations selected using purposive sampling. The analysis technique used was multiple linear regression analysis along with classical assumption tests. The results showed that partially, Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) do not have a significant effect on firm value, with significance values of 0.641, 0.248, and 0.644 (>0.05), respectively. Simultaneously, ROA, ROE, and DER have a significant effect on firm value, with an Fcount value of 3.664 > Ftable 2.83 and a significance value of 0.020 < 0.05. The Adjusted R Square value is 0.154, which means that 15.4% of the variation in firm value can be explained by ROA, ROE, and DER, while the remaining 84.6% is influenced by other variables outside the research model. Keywords: Return on Assets, Return on Equity, Debt to Equity Ratio, Firm Value, Price to Book Value Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh Return on Assets (ROA), Return on Equity (ROE), dan Debt to Equity Ratio (DER) terhadap nilai perusahaan pada perusahaan sektor Basic Materials yang terdaftar di Bursa Efek Indonesia periode 2021–2023. Nilai perusahaan diproksikan dengan Price to Book Value (PBV). Data yang digunakan adalah data sekunder yang diperoleh dari laporan keuangan tahunan. Sampel penelitian terdiri dari 15 perusahaan dengan masa pengamatan selama 3 tahun (2021–2023) sehingga diperoleh 45 pengamatan yang dipilih menggunakan teknik purposive sampling. Teknik analisis yang digunakan adalah analisis regresi linier berganda dengan uji asumsi klasik. Hasil penelitian menunjukkan bahwa secara parsial, Return on Assets (ROA), Return on Equity (ROE), dan Debt to Equity Ratio (DER) tidak berpengaruh signifikan terhadap nilai perusahaan dengan nilai signifikansi masing-masing sebesar 0,641; 0,248; dan 0,644 (>0,05). Namun secara simultan, ROA, ROE, dan DER berpengaruh signifikan terhadap nilai perusahaan dengan nilai Fhitung 3,664 > Ftabel 2,83 dan nilai signifikansi 0,020 < 0,05. Nilai Adjusted R Square sebesar 0,154 yang berarti bahwa 15,4% variasi nilai perusahaan dapat dijelaskan oleh ROA, ROE, dan DER, sedangkan 84,6% dipengaruhi oleh variabel lain di luar model penelitian. Kata kunci: Return on Assets, Return on Equity, Debt to Equity Ratio, Nilai Perusahaan, Price to Book Value